On yield regulation for sustainable forestry, with examples from Queensland - Vanclay, J.K. (Oxford Forestry Institute, 1999)
Personal anecdotes are used to highlight some important considerations for yield regulation and to introduce some pertinent literature. A checklist of key issues and research needs is offered. Perhaps the most important consideration is to maintain a holistic systems view, and to involve clients and to ensure their needs are met.